Burning the Midnight Oil: A Focus Group Study of Medical Student Night Call Preferences. (1st June 2016) - Scott, O; Novak, C; Lee, J; Forbes, K
Abstract: BACKGROUND: Call is an integral component of clerkship, providing unique clinical and educational opportunities. Recently, traditional call has been the subject of scrutiny, resulting in changes to call requirements. Canadian Pediatric clerkships currently employ a variety of call modalities, including night float, evening call, and overnight call. OBJECTIVES: To explore the impact that call modalities have on medical students, and elucidate preferences. DESIGN/METHODS: We conducted focus groups of 5-7 medical students each. Participants were asked about their experiences with various call systems during clerkship. Verbatim transcripts were analyzed independently by 2 team members using grounded-theory. All codes were further reviewed by the Principal Investigator. RESULTS: Thirty-eight students participated in 6 focus groups. Four over-arching themes were identified as influencing call preferences: (1) Educational value, including patient volume and variety, hands-on experience, and teaching; (2) Quality of life, including fatigue/burn-out, ability to maintain a healthy lifestyle, and free time; (3) Continuity and quality of patient care; (4) Contribution to professional identity and acquisition of CanMEDS roles. Overnight call was described as a "rite of passage", contributing to improved time management skills, a sense of collegiality, and self-perception as future physicians. With traditional call, post-call days provide opportunity to maintain well-being, although some believe 24-hour shifts impair ability to learn. Moreover, this call modality results in the lowest patient continuity of care. With regard to night float, most students appreciate focused call duties, and enjoy consistency with residents, resulting in greater bonding and teaching. However, they have difficulty adjusting to a nocturnal schedule, and lament missing daytime educational activities during call week. Evening call has the fewest patient encounters, least teaching, and worst fatigue and burn-out. Nonetheless, this call modality has the best patient continuity of care with no loss of daytime work. Students designated overnight call and night float as their preferred modalities, with evening call being unanimously rated least favourite. Students believe that specific goal-setting, and feedback from residents and staff are lacking across all call modalities. CONCLUSION: Students emphasize educational value and quality of life as important determinants of their call experience. Interestingly, acquisition of professional attributes and continuity of care play an important role in determining call preferences. We suggest that integrating the above elements and introducing a formal "call curriculum", may make the clerkship call experience more standardized and beneficial to medical students, facilitating their growth as medical professionals.